Insertional Achilles tendinopathy in patients with Haglund's syndrome: results of computer modeling and biomechanical research - Gerasimyuk, B.; Lazarev, I.; Movchan, O.; Skyban, M. (Journal of Education, Health and Sport, 2020)
In this study, a biomechanical relationship was found between the pathological process in Haglund syndrome and secondary tendinopathy of the Achilles tendon. We have developed the calculation diagram, created computer models and determined the values of the stress-strain state of the rear foot structures in the normal and with Haglund syndrome. It was found that the maximum stress values are concentrated on the Achilles tendon, but in pathological model the stress values were significantly higher than normal in the whole range of motion of the foot. Normally, maximal stress on the calcaneus is localized on its posterior surface - on the anterior surface of the retrocalcaneal recess. In Haglund syndrome, maximum stress was recorded on the upper surface of the posterior sections of the calcaneus. Haglund syndrome is marked by overloading of the calf muscle. The results of this study explain the development of degenerative changes in the AT in patients with Haglund syndrome. It was also found that the enlarged posterior-upper part of the calcaneus is a factor in the development of insertional Achilles tendinopathy, which should also be considered when choosing further treatment.